A multi-landscape assessment of Leptospira prevalence on a diversity of small mammals - Rosli, Muhammad Zahin; Mohd Taib, Farah Shafawati; Khoo, Jing Jing; Chee, Hui Yee; Wong, Yien Ping; Shafie, Nur Juliani; Mohamed, Nor Zalipah; AbuBakar, Sazaly; Nor, Shukor Md (Springer Nature, 2023)
Leptospirosis is a major zoonotic disease, especially in the tropics, and rodents were known to be carriers of this bacterium. There was established information on Leptospira prevalence among animal reservoirs in human-dominated landscapes from previous literature. However, there was very little focus given comparing the prevalence of Leptospira in a wide range of habitats. An extensive sampling of small mammals from various landscapes was carried out, covering oil palm plantations, paddy fields, recreational forests, semi-urbans, and wet markets in Peninsular Malaysia. This study aims to determine the prevalence of pathogenic Leptospira in a diversity of small mammals across different landscapes. Cage-trapping was deployed for small mammals trappings, and the kidneys of captured individuals were extracted, for screening of pathogenic Leptospira by polymerase chain reaction (PCR) using LipL32 primer. Eight microhabitat parameters were measured at each study site. Out of 357 individuals captured, 21 (5.9) were positive for pathogenic Leptospira of which recreational forest had the highest prevalence (8.8) for landscape types, whereas Sundamys muelleri shows the highest prevalence (50) among small mammals species. Microhabitat analysis reveals that rubbish quantity (p < 0.05) significantly influenced the Leptospira prevalence among small mammals. Furthermore, nMDS analysis indicates that the presence of faeces, food waste, and exposure to humans in each landscape type also were linked with high prevalence of pathogenic Leptospira among the small mammals. This study supplements previous studies on pathogenic Leptospira prevalence across different landscape types, and the major microhabitat factors associated with Leptospira prevalence. This information is crucial for epidemiological surveillance and habitat management to curb the possibility of the disease outbreaks.